The Differences in Adaptation Between Lowland and Highland Populations - Dwimei Ayudewandari Pranatami; Indy Naurah Atiqah; Refi Mariska (DIVERSITAS HAYATI, 2023)
Indonesia is an archipelagic country with different characteristics of each island. Indonesian people face various challenges related to their geographical place of residence which can affect their body's adaptation. Apart from being influenced by race and ethnicity, habits and the outside environment greatly affect adaptation in humans. The three most striking areas that experience geographical differences in Indonesian territory are coastal communities, lowland communities and upland communities. Geographical conditions in fact provide differences in the special characteristics of each of its inhabitants. Not only related to physical development, but patterns of daily life can also be affected by differences in geographical conditions. Things that experience differences from the conditions of the population living in the highlands, lowlands and coastal areas include: The amount of hemoglobin in the blood, Food consumption patterns, Physical appearance such as height, skin color and chest shape, Prevalence of diabetes, Daily activity and work and Heart rate and lung capacity. The adaptation made by each resident in different types of geography is a necessity in order to be able to live without experiencing difficulties in carrying out daily activities. As for people in different geographies, they can still live with each other in different ages, but the general characteristics that exist will always be the same as places where they often carry out their daily activities.